2021
DOI: 10.1108/jices-12-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on computing ethics: a multi-stakeholder analysis

Abstract: Purpose Computing ethics represents a long established, yet rapidly evolving, discipline that grows in complexity and scope on a near-daily basis. Therefore, to help understand some of that scope it is essential to incorporate a range of perspectives, from a range of stakeholders, on current and emerging ethical challenges associated with computer technology. This study aims to achieve this by using, a three-pronged, stakeholder analysis of Computer Science academics, ICT industry professionals, and citizen gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Another issue of interest that was raised by some female students is the concern regarding uploading of selfies. This supports the view by Chawki and Shazly [8] that female students and staff tend to be more cautious about sharing their webcams, as they are more likely to be harassed and exposed to aggressive behaviours in an online setting. It is therefore possible that for the student (SQf2) it was important to upload a photo that would represent her image in a manner that would satisfy her.…”
Section: Frustration With the Invigilator Appsupporting
confidence: 85%
See 3 more Smart Citations
“…Another issue of interest that was raised by some female students is the concern regarding uploading of selfies. This supports the view by Chawki and Shazly [8] that female students and staff tend to be more cautious about sharing their webcams, as they are more likely to be harassed and exposed to aggressive behaviours in an online setting. It is therefore possible that for the student (SQf2) it was important to upload a photo that would represent her image in a manner that would satisfy her.…”
Section: Frustration With the Invigilator Appsupporting
confidence: 85%
“…This possibly compromises some ethical principles. During the Covid-19 emergency, many universities were unable to obtain so-called "wet signatures" for explicit consent forms from students for this new approach of using e-proctoring systems [8]. Some disparities have also been reported about the pictures taken with a webcam.…”
Section: Controversies About E-proctoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Academics who participated in a 2021 study on ethics in computer science courses noted that ethics were often considered in standalone modules in a manner that did not reflect the distributed and interrelated aspects of cross-cutting concerns. Courses also lacked coverage of the environmental impacts of ICT (Gordon et al, 2021). In a Portuguese study on engineering education, Monteiro et al (2019) found that consideration of ethics was limited, with most curricula based on a perspective where an engineer is seen as a "neutral Higher education technician".…”
Section: Challenges and Driversmentioning
confidence: 99%